Legal conflicts of interest of the revolving door - Elise S. Brezis (Bar-Ilan University, Department of Economics, 2017)
This paper analyzes the conflicts of interest arising from the "revolving door". The revolving door is a common phenomenon, and it is unlikely that most of it can be explained by "regulatory capture", a practice that is unlawful. Therefore, there is a need for a new framework. This paper proposes a framework wherein conflicts of interest arising from the revolving door are not unlawful, as is in the case of regulatory capture, but still lead to economic distortions. The paper introduces a market for bureaucratic capital, which explains why in equilibrium, the government allows this unethical, yet not unlawful, conflict of interest to persist. Our first result is that the political elite finds it optimal to allow the existence of the revolving door, as well as the creation of bureaucratic capital. The second result is that in equilibrium, the revolving door leads to an excessive level of bureaucratic capital. As a consequence, the interconnection of elites and the existence of the revolving door actually lead to lower economic growth.
Keywords: H10; H70; O11; O43; 330; elites; bureaucracy; conflicts of interest; bureaucratic capital; revolving door; economic growth